Seasonal variability of nutrient concentrations in the Mediterranean Sea: Contribution of Bio‐Argo floats. Issue 12 (31st December 2015) - Pasqueron de Fommervault, Orens; D'Ortenzio, Fabrizio; Mangin, Antoine; Serra, Romain; Migon, Christophe; Claustre, Hervé; Lavigne, Héloïse; Ribera d'Alcalà, Maurizio; Prieur, Louis; Taillandier, Vincent; Schmechtig, Catherine; Poteau, Antoine; et al.
Abstract: In 2013, as part of the French NAOS (Novel Argo Oceanic observing System) program, five profiling floats equipped with nitrate sensors (SUNA‐V2) together with CTD and bio‐optical sensors were deployed in the Mediterranean Sea. At present day, more than 500 profiles of physical and biological parameters were acquired, and significantly increased the number of available nitrate data in the Mediterranean Sea. Results obtained from floats confirm the general view of the basin, and the well‐known west‐to‐east gradient of oligotrophy. At seasonal scale, the north western Mediterranean displays a clear temperate pattern sustained by both deep winter mixed layer and shallow nitracline. The other sampled areas follow a subtropical regime (nitracline depth and mixed layer depth are generally decoupled). Float data also permit to highlight the major contribution of high‐frequency processes in controlling the nitrate supply during winter in the north western Mediterranean Sea and in altering the nitrate stock in subsurface in the eastern basin. Key Points: Five profiling floats equipped with nitrate sensors were deployed in the Mediterranean Sea Annual cycles of nutrient concentrations depicted with an unprecedented temporal resolution Major contribution of high‐frequency processes highlighted